Reinterpretasi Makna Kekerasan Terhadap Perempuan : (Studi Kajian Tematik tentang Terminologi Kekerasan dalam al-Qur’an) - Samsudin; Andaryuni , Lilik (Muhammadiyah University of Surabaya, 2024)
In principle, Islam commands through the Qur'an and the Hadith of the Prophet that the relationship between husband and wife must be good and loving. But in reality it is not always in line with the initial desire. Tensions and conflicts that arise in the household often last a long time, even domestic conflicts often end in violence. The method used in this study is the maudu'i (thematic) interpretation method. The maudu'i (thematic) interpretation method is the method of interpretation most widely used by contemporary Muslim scholars today with the aim of studying the contents of the Qur'an, because it is not complicated, complex, straight to the point, so this method is considered the most suitable for find solutions to contemporary problems. In the asbab al-nuzul surah an-Nisa verse 19, it can be seen that the Koran uses the term karaha in the context of the prohibition of violence against women which was carried out during the jahiliyah era, when at that time women were treated arbitrarily and far from humanity, that is, they were treated like inheritance and committing adultery with it. The main points of study in surah an-Nisa verse 19 are, the first emphasizes the prohibition of things that harm and harm women. Second, manners in marriage, especially to married couples. This connection gives us an understanding that in the Al-Quran provides solutions for all life, especially in the family. Keywords: Violence, Women, Thematic.